The effect of reflexology on chemotherapy-induced nausea, vomiting, and fatigue in breast cancer patients - Afitap Özdelikara; Mehtap Tan (Elsevier, 2017)
Objective: Patients receiving chemotherapy struggle with the side effects of this treatment. These side effects obligate the patients to use not only the pharmacological methods but also non-pharmacological relaxing methods. This study was conducted to determine the effect of reflexology on chemotherapy-induced nausea, vomiting, and fatigue in breast cancer patients. Methods: The study was conducted as a pretest-posttest experimental design. The study was conducted with sixty patients, thirty as the control and thirty as the experimental groups. A sociodemographic form, Rhodes index of nausea, vomiting, and retching (INVR), and Brief Fatigue Inventory (BFI) were used to collect the data. Analysis of variance, t-test, percentage calculations, and Chi-square methods were used to evaluate the data. The data obtained were assessed using the "Statistical Package for Social Science 21.0" software. Results: It was determined that the difference between the total mean scores of INVR in the experimental and control groups was significant on the onset and first and second measurements, and the difference between total mean scores of development and distress between the groups was statistically significant in the third measurement (P < 0.05). The results of the study showed that the BFI mean scores of patients in the experimental group gradually decreased in the first, second, and third measurements (P < 0.05). Conclusions: The present study proved that reflexology decreased the experience, development, distress of nausea, vomiting, and retching as well as fatigue in the experimental group. Hence, the use of reflexology is recommended for chemotherapy-induced nausea, vomiting, and fatigue.